PERGESERAN BUDAYA KESANTUNAN BERBAHASA MAHASISWA TERHADAP DOSEN MELALUI MEDIA SOSIAL WHATSAPP - Sujiono Sujiono (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Languages in the process of communication between students and lecturers are a form of noble culture. But the reality is still found by students who do not pay attention to the fluency of language when communicating with lecturers through WhatsApp social media. The purpose of this research is to analyze the shift in the culture of politeness in students' language towards lecturers through WhatsApp social media. This research uses descriptive qualitative method. This research is descriptive qualitative because it is a description of acts of politeness of the language made by students to lecturers through WhatsApp messages and then analyzed in the form of narration. The object of research is the WhatsApp document between STABN student Raden Wijaya Wonogiri and the lecturer. The results showed that there was a shift in politeness in language shown by students when communicating with lecturers through WhatsApp. Sentences used by students when communicating with lecturers pay less attention to politeness so that the sentences tend to govern, force the will, without giving greetings, introducing themselves, apologizing, and expressing thanks.